Ethics of life and death: changes in the book's content – and the philosopher‘s thinking? - Svava Sigurdardottir (Etikk i Praksis: Nordic Journal of Applied Ethics)
Over the last four decades, Vilhjálmur Árnason professor emeritus in philosophy, has been at the forefront in the academic fields of moral and political philosophy, and medical – and bioethics in Iceland. His research and in-depth understanding of the ethical aspects of medicine and life sciences in Icelandic society are demonstrated by his extensive written work on these issues. In 1993, the first edition of his book Ethics of life and death was published in Iceland, a comprehensive book on ethical issues related to healthcare, research, and public health. A second and improved edition of the book was published in 2003, and a German version in 2004. The third and latest edition was published in August 2023, which takes into account developments in the aforementioned fields in recent years, and as before with a particular focus on Iceland.